Resource scheduling optimization in cloud-edge collaboration - Shuling WANG; Jie SUN; Peng WANG; Aidong YANG (Dianxin kexue)
With the enrichment and diversification of business types, low latency, high bandwidth, data privacy and high reliability have become common requirements.Edge computing, fog computing, distributed cloud, computing power network and other solutions have been proposed, and have triggered in-depth research and exploration in industry, academia and research.There is a consensus within and outside the industry on the view that “multi-level computing power distribution and collaboration of computing power will be the mainstream of computing power structure in the future”.The problems related to resource scheduling optimization, such as computing power management, allocation, scheduling, have also become the current research hotspot and key research direction.Therefore, for the future computing power supply structure, focuses on the latest progress of resource scheduling optimization in academia and industry, the current main methodology and engineering implementation architecture was summarized.And then, for the two typical cloud edge collaboration scenarios, the analysis was carried out from the perspective of scene splitting, scheduling objectives, and solutions in turn, and the resource scheduling optimization reference schemes that adapted to the characteristics of the scenarios were analyzed and discussed respectively.